The role of semantic memory in prospective memory and episodic future thinking: new insights from a case of semantic dementia. Issue 8 (14th September 2021) - La Corte, Valentina; Ferrieux, Sophie; Abram, Maria; Bertrand, Anne; Dubois, Bruno; Teichmann, Marc; Piolino, Pascale
ABSTRACT: Prospective memory (PM), the ability to remember to execute planned actions, and episodic future thinking (EFT), the ability to imagine future personal events, are two core aspects of future-oriented cognition. The present study aimed for the first time at examining the role of semantic memory loss in PM and EFT in a single case patient (SL) at the early stage of semantic dementia. First, we investigated various types of PM as well as episodic memory of new events using a validated ecological assessment via virtual reality. Second, we examined EFT using a temporally extended version of the TEMPau task, which measures episodic aspects of remembering the past and imagining the future taking temporal distance into account. Patient SL was deficient in semantically linked event-based PM and was unable to provide any EFT for the most distant period but was preserved in other types of PM and near and intermediate EFT. These findings provide new evidence on the role of semantic memory in PM depending on the type of intention and in EFT depending on the temporal distance mirroring autobiographical memory. Finally, they point out a specific link between PM and near EFT in future-oriented cognition.